PENGARUH KOMUNIKASI PEMASARAN DAN KEUNGGULAN BERSAING TERHADAP CITRA PERUSAHAAN PADA PT. VICTORY INTERNATIONAL FUTURES - Haritza Yuliansyah, Sania Octa (Research Journal of Social Science and Economics, 2025)
Abstract Forex trading is a high risk investment and has high prospects. where a trader benefits from the difference in the value of one currency with another foreign currency which can change periodically. The large number of companies that play a role in it and the large value of money circulating in the forex market is difficult to control by certain groups, so a specific understanding is needed in determining the policies taken to achieve high profits. This study aims to analyze the Effect of Marketing Communication and Competitive Advantage on Corporate Image at PT. Victory International Futures Surabaya. In this study, data were collected through a questionnaire method to 100 respondents who were obtained using a technique, namely technique (purposive sampling). Then performed an analysis of the data obtained in the form of quantitative analysis. Quantitative analysis includes validity and reliability tests, classic assumption tests, hypothesis testing through the F test and t test as well as the analysis of the coefficient of determination (R2). The data analysis technique used is multiple linear regression analysis. The results showed that the two independent variables, namely Marketing Communication and Competitive Advantage simultaneously had a positive and significant effect on the dependent variable, namely Corporate Image. and the most dominant influence is the variable Marketing Communication. Keywords : Marketing Communication, Competitive Advantage and Corporate Image